Short and long-term temporal variation of the zooplankton in a tropical estuary (Amazon region, Brazil) - da Costa, Kelli Garboza; Pereira, Luci Cajueiro Carneiro; Costa, Rauquírio Marinho da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
Nyctemeral and seasonal distribution of the zooplankton of the Taperaçu estuary and the effect of the hydrological parameters on the dynamics of these organisms were studied in March (rainy season) and September 2005 (dry season). Zooplankton samplings were carried out during spring tides at 2-hours intervals during a 24 h period. Samples were collected with a plankton net of 120 μm mesh size. Simultaneous temperature, salinity, pH and dissolved oxygen concentration measurements were accomplished at subsurface. The estuary presented a high seasonal variation in salinity (9.1-40.0) with regimes oscillating from mesohaline to polihaline/marine during the rainy and dry season, respectively. Temperature, pH and salinity were significantly higher during the dry season. A total of 50 taxa were identified, belonging to the following groups: Arthropoda, Sarcomastigophora, Cnidaria, Mollusca, Nematoda, Platyhelminthes, Bryozoa, Chordata, Annelida and Chaetognatha. Copepods dominated quantitatively the local zooplankton with 50% of the total organisms. Total zooplankton densities oscillated from 16,491 to 397,476 ind.m-3 during the dry and rainy season, respectively. Rainfall was the principal responsible for the hydrological parameters oscillations, mainly salinity, which influenced directly the population dynamics of the zooplankton of the Taperaçu estuary.
Keywords: Zooplankton; Tropical coastal zone; Amazon litoral; North Brazil